Improvement of Seed Germination and Seedling Growth of Faba Bean (Vicia Faba L.) through Seed Priming - Sumiaya Parvin; Md. Parvez Anwar; Md. Sojib Kabiraj; Md. Harun Rashid; Swapan Kumar Paul (Turkish Journal of Agriculture: Food Science and Technology)
In a lab experiment using seed priming, the faba bean (Vicia faba L.) seed germination and seedling development were studied. Twenty different priming techniques were utilized in the study, each comprising varying concentrations of NaOCI, CaCl2, KNO3, Manitol, PEG, KCL, H2O and a control group that received no priming. Four replications of a completely randomized design (CRD) were used in the experiment. Among the three priming treatments, there were substantial differences in the seedling growth metrics and germination rate. When 500 ppm NaOCl was used as a treatment, the highest seed germination percentage (96%) was attained. Although 100 ppm PEG had the greatest germination index (42.92), 10000 ppm NaOCl had the quickest mean germination time (8.27). Additionally, at a concentration of 1500 ppm NaOCl, the greatest seedling vigor index (29.79) and maximum germination coefficient (12.28) were likewise obtained. With H2O treatment, the maximum shoot length (21.09 cm) was observed for seedling growth parameters. The largest root length was produced by a 10000 ppm KNO3 treatment (11.19 cm). With 20000 ppm KNO3, the maximum root dry weight was achieved (88.50 mg), whereas H2O produced the highest shoot dry weight (51.0 mg). Additionally, it was discovered that a treatment with 10000 ppm KNO3 had the best root-shoot ratio (0.72). The research thus supports the possible use of seed priming as a method to improve faba bean seed germination and seedling growth. NaOCl and KNO3 seemed to work best for faba bean seed germination and seedling growth.